Pelatihan Public Speaking dan Bahasa Inggris Duta Wisata Kabupaten Ponorogo - Rifa Suci Wulandari; Ratri Harida; Tomy Kartika Putra (Edumedia Solution, 2022)
This article is a report of Community Service Program aiming at giving understanding and learning experience to Ponorogo tourism ambassador in improving Public Speaking and English competency to promote tourism. The participants of this program are 20 finalists of Ponorogo tourism ambassador 2021. This one-day-training program is carried out in form of presenting, practicing directly, doing demonstration, and simulation. Furthermore, Public Speaking materials presented are the basic technique of Public Speaking, solving anxiety in Public Speaking, the breathing technique of Public Speaking, the vocal technique of Public Speaking, Public Speaking preparation, the opening technique of Public Speaking, the material delivering of Public Speaking, and the closing technique of Public Speaking. English materials covered greeting expressions, asking and giving information, and explaining tourism object. After the materials presentation, all the participants should get throughdirect practice on delivering Public Speaking in English about tourism. Generally, the participants are active and enthusiastic. All participants can follow and perform direct demonstration related to the materials given. There are still mistakes they have done in using grammar and pronouncing some English words. However, they show their best efforts understanding the material. At the end of this program, the participants are expected to have learning experience as one of their asset to sharpen Public Speaking ability and foreign language proficiency, especially English.